Strukturelle Schwäche der russischen Wirtschaft - Galina Kolev (Wirtschaftsdienst, 2016)
Die Lage der russischen Wirtschaft ist dramatisch. Um 3,7% ist die gesamtwirtschaftliche Leistung 2015 eingebrochen. Die verhängten Wirtschaftssanktionen sowie der Ölpreisverfall haben zu der Abwärtsspirale beigetragen. Doch die eigentlichen Schwächen der russischen Wirtschaft sind eher struktureller Natur. Die starke Abhängigkeit vom Öl- und Gasgeschäft, Korruptionsprobleme, Rückschritte bei der Privatisierung und eine ineffi ziente Nutzung des vorhandenen Humankapitals erfordern mehr Entschlossenheit von der Regierung, um die Rückkehr zum Wachstumspfad zu ermöglichen. – – The economic situation in Russia is dramatic. GDP decreased by alarming 3.7 per cent in 2015. The imposed economic sanctions as well as the fall in oil prices have contributed to the downward spiral. However, the real weaknesses of the Russian economy are more structural in nature. The strong dependence on the oil and gas business, corruption problems, setbacks in privatisation efforts and the ineffi cient use of the existing human capital require greater commitment on the part of the government to commit to a return to a sustainable growth path. Individual sectors and companies in Germany suffered considerable losses of revenue in the course of the economic crisis in Russia. Overall, however, the effect on the German economy has been rather moderate.
Keywords: L11; L51; L94; Q41; Q48; 330; Konjunktur; Wirtschaftskrise; Wirtschaftsstruktur; Wachstumspolitik; Russland